Preparation and Characterization of TiO2 Nanoparticles via a Sol- gel Method - satar, maryam; Olfat A. Mahmood; Zainab N. Jameel (ASJ - Academic Science Journal, 2025)
TiO2 nanoparticles (NPs) were prepared by the sol-gel method by using TiCl4 as a startingmaterial, whereas the applied temperatures were 450 °C and 900 °C. The XRD results showedthat nanoparticle (TiO2 NPs) anatase and rutile phases had a polycrystalline nature with atetragonal structure. FESEM results showed the formation of nanostructures with cauliflowerand irregular shapes with average particle sizes of 36.9 nm and 58 nm for the Anatase and Rutilephases, respectively. The EDS spectra showed that the elements present in the synthesized TiO2NP (anatase and rutile) phases were Ti and oxygen O. The FTIR spectra of TiO2 NPs showedthe presence of broadband at 450–4000 cm−1corresponding to the stretching vibration ofterminating hydroxyl groups in the samples. The UV‒Vis-NIR absorbance spectra wererecorded in the range of 300–900 nm to investigate the optical characteristics. Results showedthat the absorption of TiO2 in the Anatase phase is less than that of TiO2 in the Rutile phase.The optical energy gaps were 3.05 and 2.7 eV for the Anatase and Rutile phases, respectively.Keywords: TiO2, Anatase phase, Rutile phase, FE-SEM, EDS.